PENGEMBANGAN KURIKULUM SEKOLAH BERKEUNGGULAN TAHFIDZ - Isna Hidayat; Fitri Puji Rahmawati; Anik Ghufron (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this research is to find out how the development of the school curriculum can be carried out with the existence of superior programs, one of which is the tahfidz program. The type of research used in this article is qualitative research using library research method by adding some case studies or implementation examples that have been applied in several schools. Data collection is done by finding sources and reconstructing from various sources such as books, journals, and existing research. The results of this study explain that curriculum development is an important part of maintaining the existence of educational units in the face of changing times. The development of a curriculum with tahfidz excellence has had a real positive impact on students, teachers, parents and schools. The implementation of the Qur'an tahfidz program in education units must be adjusted to the conditions that exist in each education unit by considering all the possibilities and also the carrying capacity owned and the challenges that must be faced by the education unit.